(untitled) (International Journal of Engineering and Computer Science, 2014)
VANET is the most popular mobile Ad-hoc network which is called Vehicular Ad Hoc Network. The researchers work a lot on this network on various parameters of the same. From the Literature review, VANETs works on the basis of real time system where the vehicles act as mobile nodes and travel with a very high speed on the roads in the urban areas. There are a number of security issues like authentication, intelligent system approach, collision detection, jamming avoidance, communication system approach etc. We basically deal with the delay issue in case of accident on the route. Here we are presenting an intelligent route identification approach in case of accident occurrence for V2V communication. If some accident takes place over the network, the neighbor node information flow will be performed to perform the route analysis. An optimal path is selected from the existing one using the min and max variants of ACO. In this work a bio inspired V2V communication approach is suggested to identify the safe path over the network. We have used the Max-Min ant system (MMAS) to achieve our goal of finding the optimal path for vehicles thus reducing the delay caused due to collisions.